(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The modern system of education of Ukraine is in an update. The problem of application outof-date methods and technologies on the lessons by teachers became the main problem now, there is a necessity of introduction new innovations. Quest-technology is includeded into the educational process of the Zaporizhia region since 2012. By today there have been a lot of quests for teachers and students of the All Ukrainian and regional levels. Teachers-innovators appear growingly which use this technology for development of children’s abilities and skills in 21 century. But the conducted pedagogical research showed that teachers, in most cases, are not ready to use the innovation and high-quality realization of quest requires precondotioning of teacher. For this purpose there the educational courses of internal and distance form were developed by the department of informatics and information technologies in education. In the conditions of financial crisis, a basic accent was done on the distance form, that was allowed to entrap the greater amount of teachers with less financial expenses. For distance course the platform Moodle was chosen and the training complex was developed. This articleis presented the distance course for teaching staff "Introduction of quest technologies in the educational process," also it is presents the results of the realization of the course in the Zaporizhja Region.